Changes in Blood Coagulation and Fibrinolysis in Rats Fed Atherogenic Diets - Merskey, Clarence; Wohl, Herbert (Thrombosis and Haemostasis, 1963)
1. Groups of rats were fed thrombogenic diets and the effects on blood coagulation and fibrinolysis assessed.2. Animals fed a diet containing cholesterol, thiouracil and cholic acid developed high levels of coagulation factors I, II, V, VII—X, VIII, IX and X.3. Animals fed a similar diet with additional 40% beef fat developed even greater elevation of V, VII—X, VIII and X, similar elevation of factor II, and lesser (but still significant) elevation of factors I and IX. In addition marked elevation of blood platelets occurred.4. Euglobulin lysis time of the group not fed the additional fat was longer than in controls. Significant prolongation of euglobulin lysis time was not found in the group fed additional fat.5. If the increased levels of plasma fibrinogen were taken into account, it was found that a larger amount of fibrin was lysed per unit time in the euglobulin lysis test with plasma from rats fed either atherogenic diet compared with controls.6. Defective thromboplastin generation was present in both groups of rats fed an atherogenic diet. The defect was present in the serum and was not due to lack of a factor required for thromboplastin generation. An inhibitor was present in the serum which was capable of preventing the action of normal serum.7. No good correlation was found between the occurrence of changes in blood coagulation or fibrinolysis and the presence or absence of thrombosis and infarction.8. The exact cause of these anomalies remains unexplained, as does the cause of the thrombosis in these animals. Starvation per se does not account for these abnormal findings. They could not adequately be explained on the basis of “hypercoagulability” of the blood.